Optineurin-mediated mitophagy as a potential therapeutic target for intervertebral disc degeneration - Hu, Zhilei; Wang, Yu; Gao, Xiaoxin; Zhang, Yuyao; Liu, Chenhao; Zhai, Yu; Chang, Xian; Li, Haiyin; Li, Yueyang; Lou, Jinhui; Li, Changqing (Frontiers in Pharmacology, 2022)
Low back pain (LBP) is thought to be mainly caused by intervertebral disc degeneration (IVDD), and there is a lack of effective treatments. Cellular senescence and matrix degradation are important factors that cause disc degeneration. Mitochondrial dysfunction induced by oxidative stress is an important mechanism for cellular senescence and matrix degradation in the nucleus pulposus (NP), and mitophagy can effectively remove damaged mitochondria, restore mitochondrial homeostasis, and mitigate the damage caused by oxidative stress. Optn is a selective mitophagy receptor, and its role in IVDD remains unclear. Here, we aimed to explore the effect of Optn on H2O2-induced nucleus pulposus cell (NPC) senescence and matrix degradation in a rat model of degenerative discs. Western blotting showed that Optn expression was reduced in degenerative human and rat NP tissue and increased in H2O2-induced senescent NPCs. Optn overexpression significantly reduced the H2O2-induced decrease in senescence and matrix-associated protein expression in NPCs, and Optn knockdown showed the opposite effect. Previous reports suggested that mitophagy significantly reduced mitochondrial damage and reactive oxygen species (ROS) caused by oxidative stress, and we used the mitophagy agonist CCCP, the mitophagy inhibitor CsA, and the mitochondrial ROS scavenger mitoTEMPO to confirm that Optn attenuated NPC senescence and matrix degeneration caused by oxidative stress by promoting mitophagy to scavenge damaged mitochondria and excess ROS, thereby slowing the progression of IVDD. In conclusion, our research suggests that Optn is involved in IVDD and shows beneficial effects on IVDD.